2012
DOI: 10.1186/1471-2296-13-71
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of care planning in England: interviews with patients with long term conditions

Abstract: Background The prevalence and impact of long term conditions continues to rise. Care planning for people with long term conditions has been a policy priority in England for chronic disease management. However, it is not clear how care planning is currently understood, translated and implemented in primary care. This study explores experience of care planning in patients with long term conditions in three areas in England. Methods We conducted semi-structured interviews … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
82
0
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(89 citation statements)
references
References 22 publications
3
82
0
4
Order By: Relevance
“…This is a strategy that health services and social services use to support patients in their care, and that can result in the organization of a care plan in the form of a document with definition of agreed goals. 7 This model is also understood as a process of cooperation between a health professional, the patient with complex conditions and the social support network, to plan, monitor and evaluate care alternatives, in order to provide a qualified care, that may increase the functional ability and preserve the individual and family autonomy. 5 The English Department of Health seeks a care planning based on case management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a strategy that health services and social services use to support patients in their care, and that can result in the organization of a care plan in the form of a document with definition of agreed goals. 7 This model is also understood as a process of cooperation between a health professional, the patient with complex conditions and the social support network, to plan, monitor and evaluate care alternatives, in order to provide a qualified care, that may increase the functional ability and preserve the individual and family autonomy. 5 The English Department of Health seeks a care planning based on case management.…”
Section: Discussionmentioning
confidence: 99%
“…One study found that when patients are assisted based on case management, they felt surprised and were not familiar with the term "care planning". 7 Other studies reported that case management can improve the quality of communication between the health team and patients and help to satisfy those involved in the experience of care, whether doctors, patients or families. 8,16,19 The use of the GRACE and PACE models and Gundersen program, patients reported receiving more information about their conditions, they had fewer needs that were not cared for, and the last aspect led to change the outbreak of the disease for the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Hal ini sesuai dengan penelitian Newbould et al, (2012) bahwa dalam perencanaan kegiatan home care, dibutuhkan diskusi bersama antara pasien dengan perawat. Karena dalam kegiatan perencanaan tidak hanya terkait rencana tindakan dan jadwal perencanaan tetapi diperlukan adanya kesepakatan terkait output kegiatan…”
Section: Sumber Dayaunclassified
“…It requires the 4 following inter-dependent elements: 1) engaged and informed patients; 2) healthcare professionals committed to partnership working; 3) facilitative organisational structures & 4) supportive commissioning processes [15]. Although adoption in practice has been variable [16,17], formal evidence of effectiveness of care planning is beginning to emerge [13,15,18,19].…”
Section: Coherence (Sense-making Work)mentioning
confidence: 99%
“…We used NPT to describe the steps undertaken by practitioners in making sense of the care planning model and adapting it to their particular practice contexts. As such, this paper responds to calls for research to further understanding of the ways that care planning is integrated and embedded in primary care for people with complex needs [17].…”
Section: Coherence (Sense-making Work)mentioning
confidence: 99%